Effect of Fermentation on the Proximate and Antinutrient Composition of Banana Peels - P.T, Ozabor; A.O, Ojokoh; A.A, Wahab; O.O, Aramide (The International Journal of Biotechnology, 2020)
This study was carried out to investigate the effect of fermentation on the physicochemical and microbiological properties of banana peels with the view of reducing environmental pollution. Bacteria and fungi responsible for the fermentation were isolated and characterized using standard microbiological techniques. A total of 11 microorganisms were isolated and identified as: Bacillus substilis, Lactobacillus fermentum, Micrococcus luteus, Pseudomonas aeruginosa, Staphylococcus aureus, Aspergillus flavus, Mucor mucedo, Rhizopus stonifer, Aspergillus niger, Saccharomyces cerevisae and Penicillium frequentans. The pH of the samples decreased from 6.88 at 0 hr to 4.80 at 72 hr of fermentation while the titratable acidity increased from 0.21 g/l at 0 hr to 0.36 g/l at 72 hr of fermentation. The results of the proximate analyses revealed that there was a decrease in the ash (15.30 to 5.67%), fat (13.15 to 8.53%) and protein (13.72 to 10.09%) contents after fermentation. The moisture ( 8.28 to 13.28% ) , crude fibre (15.29 to 32.08%) and carbohydrate (29.24 to 35.32%) contents and the energy value also increased from 1087.14 to 1217.75kj/g after fermentation. Results of the anti-nutrient composition shows that there was reduction in Phytate (12.66 mg/g to 9.27mg/g ), oxalate (33.31 mg/g to 8.28 mg/g), glycosides (256.19 mg/kg to 149.02 mg/kg), Phenol (8.06% to 4.15 %), Tannin (7.01 mg/g to 3.79 mg/g) and Phytic acid (3.52 mg/g to 2.68 mg/g) contents after fermentation. Therefore, it can be concluded from this study that fermented banana peels are rich in nutrients needed in the formulation animal feeds.